Taking a stand: regaining power by purchasing controversial brands - Gomes, Marta Carvalho (2020)
People want to escape theaversive state of powerlessness,asitmakes them feel out of control and induces negative effects. One waythrough which peopleresolvethe absenceof personal control iscompensatory consumption. This work theorizes that powerless individuals will consume more controversial brands because theyare perceived by those individuals as powerful. Byconducting anexperimental study, in whichbrand controversy was manipulated via twoscenarios, no evidence was foundtosupportthemainhypothesis.Unexpectedly, it was found that controversial brands are perceived as less powerful by powerless individuals than by powerful individuals.